Protective Effect of Ethanolic Extracts of Ananas Comosus and Vitis Vinifera Against Glucose Induced Cataract in Isolated Goat Lens - Jenifer, Threkha; Vasanthakumar, Mahesha; Manoharan, Keerthana (Asian Journal of Biological and Life Sciences, 2024)
Background: Cataracts represent the significant basis of blindness worldwide that averts the passage of light from the clear lens to the retina. The antioxidants present in natural sources are known to delay the formation of cataracts. These antioxidants are the major constituents of fruits. Materials and Methods: This study aimed to evaluate the fruits Ananas comosus and Vitis vinifera for their antioxidant and anticataract activities against the cataract induced by glucose in the freshly isolated goat lenses which was extracted by extracapsular method and were split into six groups with six goat lenses each. Group I was the normal control, Group II was cataract control, Group III was A. comosus extract treated lens, Groups IV and V were V. vinifera extract (green and black grapes) treated respectively and Group VI was treated with the standard drug Enalapril. The opacity of the lens was assessed after incubation and lens homogenate was evaluated for antioxidant enzymes and also for lipid peroxidation. Results: The ethanolic fruit extracts of Ananas comosus and Vitis vinifera showed significant antioxidant activity in In vitro methods and also good anticataract activity in the isolated goat lens which could be caused by the action of the phytochemicals. Conclusion: From the present study on the glucose induced cataractogenesis in the isolated goat lenses, it can be concluded that the ethanolic fruit extracts of Ananas comosus and Vitis vinifera exhibit significant antioxidant and anticataract activities.
Keywords: Ananas comosus; Antioxidants; Cataract; Fruits; Goat lens; Vitis vinifera